Proceedings of 11th Symposium on Nuclei in the Cosmos — PoS(NIC XI) 2011
DOI: 10.22323/1.100.0288
|View full text |Cite
|
Sign up to set email alerts
|

Chemical abundances in metal-poor giants: limitations imposed by the use of classical 1D stellar atmosphere models

Abstract: In this work we have used 3D hydrodynamical (CO 5 BOLD) and 1D hydrostatic (LHD) stellar atmosphere models to study the importance of convection and horizontal temperature inhomogeneities in stellar abundance work related to late-type giants. We have found that for a number of key elements, such as Na, Mg, Si, Ca, Ti, Fe, Ni, Zn, Ba, Eu, differences in abundances predicted by 3D and 1D models are typically minor (< 0.1 dex) at solar metallicity. However, at [M/H] = -3 they become larger and reach to -0.5 . . .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Remarkably, at [M/H] = −3.0 this may result in differences A&A 549, A14 (2013) of up to −1.0 dex in the abundances of chemical elements derived with the 3D hydrodynamical and classical 1D model atmospheres. This result was later confirmed by Dobrovolskas et al (2010) and Ivanauskas et al (2010), who used different 3D hydrodynamical stellar atmosphere and spectrum synthesis codes, CO 5 BOLD and Linfor3D, respectively, together with the atmospheric parameters of red giants similar to those utilized by Collet et al (2007). All these studies unequivocally point to the fact that the role of convection in the atmospheres of red giant stars may be significantly more important than previously thought, especially at metallicities [M/H] < ∼ −1.0.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Remarkably, at [M/H] = −3.0 this may result in differences A&A 549, A14 (2013) of up to −1.0 dex in the abundances of chemical elements derived with the 3D hydrodynamical and classical 1D model atmospheres. This result was later confirmed by Dobrovolskas et al (2010) and Ivanauskas et al (2010), who used different 3D hydrodynamical stellar atmosphere and spectrum synthesis codes, CO 5 BOLD and Linfor3D, respectively, together with the atmospheric parameters of red giants similar to those utilized by Collet et al (2007). All these studies unequivocally point to the fact that the role of convection in the atmospheres of red giant stars may be significantly more important than previously thought, especially at metallicities [M/H] < ∼ −1.0.…”
Section: Introductionmentioning
confidence: 54%
“…This approach allowed us to cover a range in λ c and χ to quantify the trends of line formation properties in the 3D hydrodynamical and 1D classical model atmospheres with respect to these two line parameters. Conceptually, this method can be traced back to the work of Steffen & Holweger (2002) and was applied in several later studies too (e.g., Collet et al 2007;Dobrovolskas et al 2010;Ivanauskas et al 2010). Synthetic line profiles were calculated for the following tracer species of astrophysical interest: Fictitious lines were calculated at three wavelengths, λ c = 400, 850, and 1600 nm.…”
Section: One-dimensional (1d) Modelmentioning
confidence: 99%
“…Even considering that the atmospheric parameters are not exactly the same in both their and our models, the corrections of Collet and collaborators appear noticeably larger. This is also the case for other species (see Ivanauskas et al 2010;Dobrovolskas et al 2010) and the reason is not yet understood.…”
Section: Abundance Corrections For the Hf R9 And Forbidden O Linesmentioning
confidence: 94%
“…However, the positive sign of the 3D-1D abundance differences indicates that in the spectra of red giants in NGC 6752 the three studied Ba II lines will be weaker in 3D than in 1D, in contrast to what is generally seen in red giants at this metallicity (cf. Collet et al 2007;Dobrovolskas et al 2010). …”
Section: The 3d-corrected 1d Nlte Barium Abundance In Ngc 6752mentioning
confidence: 99%
“…A step beyond these limitations can be made by using threedimensional (3D) hydrodynamical atmosphere models that account for the three-dimensionality and non-stationarity of stellar atmospheres from first principles. Recent work has shown that significant differences may be expected between stellar abundances derived using 3D hydrodynamical and classical 1D model atmospheres (Collet et al 2007(Collet et al , 2009González Hernández et al 2009;Ramírez et al 2009;Behara et al 2010;Dobrovolskas et al 2010;Ivanauskas et al 2010; see also Asplund 2005, for a review of earlier work). These differences become larger at lower metallicities and at their extremes may reach 1 dex (!…”
Section: Introductionmentioning
confidence: 99%